Late Paleogene saline lake evolution of the Ningnan Basin and its response to the regional paleoclimate and uplift of the Tibetan Plateau: Evidence from sedimentary strata, and S and Sr isotopes. (22nd December 2017) - Wu, Xiaoli; Li, Rongxi; Hu, Jianmin; Li, Delu; Zhao, Bangsheng; Liu, Futian; Cheng, Jinghua; Qin, Xiaoli
Abstract : A saline lake developed in the Ningnan Basin during the sedimentation of the Qingshuiying Formation in the Late Paleogene. In order to research the evolutionary characteristics of the saline lake and its response effect to the regional paleoclimate and uplift of the Tibetan Plateau in the Late Paleogene, the Hejiakouzi section of Qingshuiying Formation in the north of the Ningnan Basin was selected. The features of the strata, gypsum petrology, and S and Sr isotopes of synsedimentary gypsum were studied. Furthermore, the relationship of the evolution of the saline lake to the regional paleoclimate and the uplift of the Tibetan Plateau are discussed. The results showed that the lithology of Qingshuiying Formation was mainly celadon‐aubergine mudstone and gypsum. S and Sr isotopic values of synsedimentary gypsum were 8.2–12.3‰ and 0.7105–0.7113, respectively. The sedimentary environment of Qingshuiying Formation was generally a weak continental saline lake, which can be further divided into 4 kinds of sedimentary environment, namely deep saline lake, semi‐deep saline lake, shallow saline lake, and brackish lake. At 45–40 Ma, the first uplift of the Tibetan Plateau occurred with a humid climate, and a brackish lake was mainly germinated. At 40–30 Ma, the climate was dry and hot, and deep and semi‐deep saline lakes mainly developed. At 30–27 Ma, the climate became dry and cold, and a shallow saline lake mainly developed. At 27–23 Ma, the second uplift of the Tibetan Plateau occurred, the climate became humid and cold due to the East Asian summer monsoon, and a brackish lake mainly developed, and the evolution of saline lake was completed by this time.